Optimized Strengthening Based on Concrete Jacketing for Minimum Eccentricity - Mitropoulou, Chara Ch.; Naziris, Iordanis A.; Kallioras, Nikos Ath.; Lagaros, Nikos D. (Frontiers in Built Environment, 2022)
Coupled lateral-torsional response is observed in building structures subjected to dynamic excitation due to lack of symmetry in terms of mass and/or stiffness in any of storeys’ plan view; such structural systems are called eccentric. A large percentage of damages, and even collapses, concerns building structures with asymmetric plan views. Combined torsional-translational vibration of their structural system result to higher ductility demands especially to vertical structural elements located at the perimeter of the plan view. In this study the minimization problem of the torsional response of an eccentric, multi-storey reinforced concrete (RC) building is examined, by strengthening its vertical structural elements with RC jackets. The problem of minimizing the eccentricity between mass and rigidity centres for all storey layouts together with the corresponding minimization problem of the eccentricity between mass and strength centres also for all stories are considered as two separate formulations for the reduction of the tortional response optimization problem. Based on recent studies the centre of strength is considered as more preferable for assessing the torsional response of buildings in case of inelastic response. For solving the two optimization problems, Imperialist Competitive Algorithm (ICA) that is member of the family of evolutionary search algorithms, is used. The optimization problems are formulated for the case study building considered after assessing its structural behaviour and capacity by means of nonlinear static analyses before and after strengthening. The later process was implemented in order to meet code requirements and examine the improvements achieved through optimization.